Ferramenta BIM de análise automatizada de projetos - Carvalho, Yan Mota Veras de (2021)
The BIM design process reveal possibilities to use information contained in the models to improve designs. One of the main aspects of applying BIM is the ability to evaluate and check designs. This work proposes the use of visual programming languages to automate the design performance checking, to improve the design process. The research is developed following the Design Science Research composed of the following steps: identification of the state of the art for automated evaluation of BIM models; selection of performance criteria to be evaluated; transformation and coding of rules; tests and pilot project; and framework proposal for evaluation criteria development. The artifact developed in visual programming through the integration of Dynamo with Revit evaluates models through 43 automated criteria, in 4 dimensions: Constructability, Sustainability, Flexibility and Conformity. Based on this artifact, a framework is presented with activities, classification tools and procedural definitions that generalize the applied method.